Inovasi Kebijakan Inklusi Keuangan Melalui Penyusunan Data Nasional Terpilah Gender (DNTG) - Ifa, Fauziatul; Sahdana, Luthfi Sabda (Sanskara Akuntansi dan Keuangan, 2025)
The purpose of this research is to describe best practices and analyze the success of Financial Inclusion Policy Innovation through the Compilation of Gender Disaggregated National Data (DNTG). The method used in this research is descriptive qualitative. Data collection techniques used seminars and literature studies. The types of data collected are primary data and secondary data. The criteria from Prasojo's theory, used to measure the success of innovation are impact, cooperation, sustainability, and leadership. The results of this study found that the impact of innovation can provide useful information in government policies and private sector practices and can improve financial literacy for women and access to financial services. Cooperation and coordination between ministries/institutions, financial services (banks), financial services (non-banks), fintech companies, and Islamic financial institutions. The DNTG will continue and be updated regularly so that it can be used as a reference by various stakeholders. The Coordinating Ministry for Economic Affairs continues to be committed to providing great opportunities for access to formal finance for women, in addition to gender mainstreaming in the medium-term development plan.